2013
DOI: 10.1186/gm428
|View full text |Cite
|
Sign up to set email alerts
|

Personal genome testing in medical education: student experiences with genotyping in the classroom

Abstract: BackgroundDirect-to-consumer (DTC) personal genotyping services are beginning to be adopted by educational institutions as pedagogical tools for learning about human genetics. However, there is little known about student reactions to such testing. This study investigated student experiences and attitudes towards DTC personal genome testing.MethodsIndividual interviews were conducted with students who chose to undergo personal genotyping in the context of an elective genetics course. Ten medical and graduate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 22 publications
2
74
0
1
Order By: Relevance
“…This apparent contradiction between perceived need and lack of use of counseling services is consistent with other educational trials of PGT. 13,31 We believe the program's focus on ethics training (expert lecturer, active discussions, the 4-week PGT decision-making period, and genetics counselor availability) was important in supporting students regarding potential psychosocial issues. Other investigators further advocate for student access to a multidisciplinary approach to consultative services (not just genetic counselors).…”
Section: Discussionmentioning
confidence: 99%
“…This apparent contradiction between perceived need and lack of use of counseling services is consistent with other educational trials of PGT. 13,31 We believe the program's focus on ethics training (expert lecturer, active discussions, the 4-week PGT decision-making period, and genetics counselor availability) was important in supporting students regarding potential psychosocial issues. Other investigators further advocate for student access to a multidisciplinary approach to consultative services (not just genetic counselors).…”
Section: Discussionmentioning
confidence: 99%
“…According to another study, physicians found utility in providing PGx testing to improve patient outcomes by individualizing treatment to guide medication decisions and to decrease time and cost for maximizing the benefits of needed medications [35]. Utilizing PGx testing in order to avoid side effects from medication and improve medication effectiveness have been proposed as benefits in other studies as well [5,17,20,[35][36][37].…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 99%
“…In order for PGx testing methods to be most effective, stakeholders, such as physicians, will need to better understand the process themselves in order to provide recommendations of such testing to their patients [20,35]. Other studies conducted with medical, graduate and pharmacy students who underwent personal genomic testing, which included PGx-related data, also revealed that this testing provided insight into the patient experience and increased understanding of genetic concepts [37][38][39][40]. Another study of physician assistant students who were specifically offered CYP2D6 testing reported similar results and noted that further exposure to PGx testing during rotations influenced perceptions of clinical utility as well [41].…”
Section: Re Sending Their Cheek Cells Off That Their Dna Is Getting Smentioning
confidence: 99%
“…3,[9][10][11] Despite several institutions offering personal genomic testing within the educational setting, only one-Stanford-has published results regarding students' experiences in these courses. 12,13 They used direct-to-consumer genotyping. As costs decrease, WGS will increasingly become the standard technology for clinical genomics.…”
Section: Introductionmentioning
confidence: 99%